Neuropsychiatric systemic lupus erythematosus is associated with imbalance in interleukin 10 promoter haplotypes. Issue 2 (1st February 1999) - Rood, M J; Keijsers, V; van der Linden, M W; Tong, T Q T; Borggreve, S E; Verweij, C L; Breedveld, F C; Huizinga, T W J
Abstract : OBJECTIVE: To investigate the association of interleukin 10 (IL10) promoter polymorphisms and neuropsychiatric manifestations of systemic lupus erythematosus (SLE). METHODS: IL10 haplotypes of 11 healthy volunteers were cloned to confirm that in the Dutch population, only the three common haplotypes (-1082/-819/-592) GCC, ACC and ATA exist. The IL10 promoter polymorphisms of 92 SLE patients and 162 healthy controls were determined. The medical records of the SLE patients were screened for the presence of neuropsychiatric involvement. RESULTS: All cloned haplotypes were either GCC, ACC or ATA. Forty two SLE patients had suffered from neuropsychiatric manifestations (NP-SLE). In NP-SLE patients, the frequency of the ATA haplotype is 30% versus 18% in the controls and 17% in the non-NP-SLE group (odds ratios 1.9, p=0.02, and 2.1, p=0.04, respectively), whereas the GCC haplotype frequency is lower in the NP-SLE group compared with controls and non-NP-SLE patients (40% versus 55% and 61%, odds ratios 0.6, p=0.02 and 0.4 p=0.006). The odds ratio for the presence of NP-SLE is inversely proportional to the number of GCC haplotypes per genotype when the NP-SLE group is compared with non-NP-SLE patients. CONCLUSIONS: The IL10 locus is associated with neuropsychiatric manifestations in SLE. This suggests that IL10 is implicated in the immunopathogenesis of neuropsychiatric manifestations in SLE.